Community involvement and development: An inter-marriage of ISO 26000 and millennium development goals. Issue 9 (2nd September 2014) - Katamba, David; Marvin Nkiko, Cedric; Tushabomwe Kazooba, Charles; Kemeza, Imelda; Babiiha Mpisi, Sulayman
Abstract : Purpose: – The purpose of this paper is to explore how ISO 26000 inter-marries with millennium development goals (MDGs) with a view to demonstrate and recommend how businesses can successfully use this intermarriage to solve society problems. Design/methodology/approach: – Case methodology was used to investigate how a company can use the social responsibility standard, ISO 26000, to guide its corporate social responsibility (CSR) aimed at contributing to MDGs. The paper focussed on the CSR dimension of community involvement and development (CI&D) interventions in health-related MDGs (4, 5 and 6). Data collection was by semi-structured interviews with CSR managers of the studied company, plus non-participant observation of CSR activities and projects. In order to develop a framework within which the collected data could be analyzed, the authors employed pattern-matching, explanation building and time series analysis. For generalization purposes of findings, the authors were guided by the "adaptive theory approach." Findings: – The intermarriage is much revealed in health and wellness. This intermarriage also reveals cross-cutting issues which support universal access to health care and prevent illnesses. Lastly, the intermarriage is symbiotic in nature, that is, MDGs contribute what to achieve while ISO 26000 contributes how to achieve. Research limitations/implications: – The case study (Uganda Baati Ltd, - UBL) that informed this research is a subsidiary company of a multinational, SAFAL Group. This provided an indication that global or trans-national forces drive CSR/CI&D at UBL. Thus, the findings may not fit directly with a company that has a local/national focus of its CSR/CI&D. Practical implications: – The paper presents guidelines to use and localize this intermarriage so as to focus CSR on global socio-economic development priorities, identify strategic stakeholders, and pathways to solutions for complex CI&D issues. Originality/value: – This research advances the Post-2015 MDG Development Agenda suggested during the United Nations MDG Summit in 2010 which called for academic contributions on how MDGs can be realized even after 2015.